2019
DOI: 10.4046/trd.2019.0006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Physical Activity and Lung Function in Dusty Areas: Results from the Chronic Obstructive Pulmonary Disease in Dusty Areas (CODA) Cohort

Abstract: BackgroundAlthough physical activity is known to be beneficial to lung function, few studies have been conducted to investigate the correlation between physical activity and lung function in dusty areas. Therefore, the purpose of this study is to investigate the correlation between physical activity and lung function in a Korean cohort including normal and COPD-diagnosed participants.MethodsData obtained from the COPD in dusty areas (CODA) cohort was analyzed for the following factors: lung function, symptoms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…(11) During the warm/summer season, for example, elderly patients should try to stay inside during daytime in order to prevent ozone exposure as much as possible. Such recommendation may lead to a decrease in physical activity although evidence shows the benefits of physical activity even in polluted areas (12). Therefore, potential risks and benefits should be well-evaluated in the future guidelines.…”
Section:  Mortalitymentioning
confidence: 99%
“…(11) During the warm/summer season, for example, elderly patients should try to stay inside during daytime in order to prevent ozone exposure as much as possible. Such recommendation may lead to a decrease in physical activity although evidence shows the benefits of physical activity even in polluted areas (12). Therefore, potential risks and benefits should be well-evaluated in the future guidelines.…”
Section:  Mortalitymentioning
confidence: 99%
“…Several studies have found positive associations between physical activity [1][2][3][13][14][15][16][17][18][19][20][21] and lung function levels in adults but most of them were cross sectional [15][16][17] or conducted in specific populations such as COPD patients [18] or adults with asthma [19]. A few prospective studies suggested a beneficial effect of physical activity on lung function in healthy adults [2,13,20,21] or in the general population [1,3,14], although results are inconsistent in terms of assessment of physical activity, length of follow-up or adjustment for potential confounders.…”
Section: Plos Onementioning
confidence: 99%
“…COPD is associated with decreased daily life activity, even when airflow obstruction is only mildly to moderately impaired [ 12 , 13 ]. Hence, many cardiac patients can have undiagnosed mild-moderate COPD, before they progress to a stage of severe COPD when the respiratory symptoms become very prominent [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%